Case Report: A case report of dry tap during ventriculostomy - Munakomi, Sunil (F1000Res, 2015)
Pneumocephalus following ventriculoperitoneal (VP) shunt insertion is an exceptionally rare occurrence. We report such an event after attempting ventricular puncture (ventriculostomy) for VP shunt insertion and then discuss the management of the same. Dry tap can lead to multiple attempts for ventriculostomy with the associated added risks of complications, as well as complicating the subsequent management. In addition, there is an increased risk of tension pneumocephalus, seizure and shunt failure due to a blockage by air bubbles. Our patient presented with features of raised intracranial pressure two months following craniotomy and evacuation of traumatic subdural hematoma. External ventricular puncture revealed egress of CSF under pressure. Upon attempting VP shunting for post-traumatic hydrocephalus, we experienced dry tap during ventricular puncture that complicated further management. We placed the proximal shunt in the presumed location of the foramen of Monro of ipsilateral frontal horn of lateral ventricle and did not remove the external ventricular drain. Post-operative CT scan revealed pneumoventriculi as the cause for the dry tap during ventricular puncture. Patient was managed with 100% oxygen. He showed gradual improvement and was later discharged. This case shows that variations in the procedure, including head down positioning, adequate cruciate dural incision prior to cortex puncture, and avoiding excessive egress of CSF can help to prevent such complications.